Safety Index Based on Geometric Probability Is Proposed to Represent the Uncertainty of Soil Parameters for Spread Foundations - Vadai, Zsolt; Garai, József; Kovács, Imre (International Journal of Engineering and Management Sciences, 2021)
The overall factor of safety in geotechnics can be defined as the product of four partial factors of safety. One of these partial factors represents the uncertainty of the soil parameters. Based on geometric probability, a safety index is proposed to calculate the uncertainty of the soil parameters for spread foundations. Numerical examples have also been presented.